Social uses of cultural and natural heritage - ZANIRATO, Silvia Helena (2007)
This text aims to reflect about the social uses of cultural and natural heritage, or social participation in the identification, preservation, study and dissemination of the things which constitute the identity of one community. For this, reasons for limited involvement of a significant part of the population with the safeguarding of assets and challenges that present to a democratic management of heritage policies are analyzed.